Biofertilizer Application of Rabbit Urine and Eggshell Powder Improves Purple Eggplant (Solanum melongena L.) Productivity Under Tropical Field Conditions - Yohanes Ferry Fernanda; Ramdan Hidayat; Didik Utomo Pribadi (Universitas Labuhanbatu, 2025)
Background: Eggplant (Solanum melongena L.) production in Indonesia is still low compared to the national demand of about 782,600 tons, with current production only 102,540.3 tons. To improve yields, organic fertilizers such as rabbit urine and chicken eggshells can be used, as they provide beneficial nutrients for the plants. The purpose is to determine the effects of liquid organic fertilizer (LOF) made from rabbit urine and varying doses of chicken eggshells on the growth and yield of purple eggplant (S. melongena L.). Methodology: The research was conducted in Menganti Subdistrict, Gresik Regency. The study used a Factorial Complete Randomized block Design (CRBD) with two factors: rabbit urine concentration (10, 20, 40, 80 ml/L) and chicken eggshell doses (5, 10, 15 grams/plant), observation parameter included plant morphology, fruit yield, and the quality of the fruit. ANOVA was used to analys the data. Findings: The results showed that there was no significant interaction between the two treatments on any observed parameters. The single-factor treatment of chicken eggshell dose had a highly significant effect on both vegetative and generative growth, with an optimal dose of 10 grams per plant. Meanwhile, the single-factor treatment of rabbit urine concentration had no significant effect; however, concentrations of 10–20 ml/L showed a tendency to increase plant yield. The highest fruit set percentage, 69.61%, was obtained from the combination treatment of 10 ml/L rabbit urine and 10 grams/plant chicken eggshell. Contribution: The combination of Rabbit urine and eggshell effective as a an promising biofertilizer for the optimum growth and yield of eggplant